Biliverdin Reductase: More than a Namesake – The Reductase, Its Peptide Fragments, and Biliverdin Regulate Activity of the Three Classes of Protein Kinase C - Gibbs, Peter E.; Tudor, Cicerone; Maines, Mahin D. (Frontiers in Pharmacology, 2012)
The expanse of human biliverdin reductase (hBVR) functions in the cells is arguably umatched by any single protein. hBVR is a Ser/Thr/Tyr kinase, a scaffold protein, a transcription factor and an intracellular transporter of gene regulators. hBVR is an upstream activator of the insulin/IGF-1 signaling pathway and of PKC kinases in the two major arms of the pathway. In addition, it is the sole means for generating the antioxidant bilirubin-IXα. hBVR is essential for activation of ERK1/2 kinases by upstream MAPKK-MEK and by PKCδ, as well as the nuclear import and export of ERK1/2. Small fragments of hBVR are potent activators and inhibitors of the ERK kinases and PKCs: as such, they suggest the potential application of BVR-based technology in therapeutic settings. Presently, we have reviewed the function of hBVR in cell signaling with an emphasis on regulation of PKCδ activity.